Marsdenia microcarpa, a new species of Marsdenia (Apocynaceae, Asclepiadoideae) from montane Guerrero, Mexico - Juárez-Jaimes, Verónica; Lozada-Pérez, Lucio (Phytotaxa, 2015)
A new species of Marsdenia (Apocynaceae; Asclepiadoideae) is described from the mountain cloud forest in the state of Guerrero, Mexico. Marsdenia microcarpa is distinguished from other species of the genus by its gynostegial corona lobes oblong-ovate, adnate to the gynostegium, free, erect or divergent obtuse apices, margins of lobes connate at base, corpuscle with rostrate apex, narrowly fusiform follicles of less than 5 cm at maturity. A key to the species of Marsdenia in the state of Guerrero is presented.